IMPLEMENTASI PROGRAM DIVERSIFIKASI PRODUK PANGAN LOKAL DI DINAS KETAHANAN PANGAN PROVINSI JAWA TENGAH - Riantika Aulia Putri; Ika Dyah Kumalasari; Bakti Utama (MEDIAGRO, 2022)
In Indonesia, rice is a staple food that has high carbohydrates and is consumed by all Indonesian people. The high consumption of rice in Indonesia causes a decrease in the level of consumption of non-rice food and the low consumption of animal protein, vegetables, and fruits. Until the government made the slogan "full doesn't have to be rice" and held a program to change people's mindsets, namely with a diversification program for local food products. The purpose of this analysis is to find out the results of the implementation of the Local Food Product Diversification Program in the Women Farmers Group (KWT)/ Micro Small Medium Enterprises (UMKM) and the community at the Food Security Office of Central Java Province. The analytical methods used in the Local Food Product Diversification Program through interviews and literature studies are descriptive analysis, fishbone diagrams, and Strength Weakness Opportunity Threats (SWOT) analysis. The results of the implementation of the Local Food Diversification Program for KWT/UMKM and the community are that it can increase the income/turnover of the KWT/UMKM and direct the community to consume local food to achieve the ideal Food Hope Pattern (PPH) score so as to reduce excessive rice consumption.